Design of high speed Wallace tree multiplier using 8-2 and 4-2 adder compressors - Jagadeeswara Rao, E; Jayaram Kumar, K; T. V. Prasad, Dr. (International Journal of Engineering and Technology, 2018)
Multiplication is one of the most common arithmetic operations employed in digital systems such as FIR filters and DSP processors but multipliers are the most time, area, and power consuming circuits. Improvement in any of these parameters can be advantageous for improv-ing the efficiency of the circuit. High-speed multiplier which uses the high-speed adder is designed based on the Wallace tree concept in this paper. In this paper first we present an approach towards the reduction of delay in Wallace tree multipliers by using 8:2 and 4:2 adder com-pressors, in the partial product reduction stage. The proposed design is also compared to the Wallace Tree multiplier which uses 4:2 and 8:2 adder compressors in terms of propagation delay. The proposed design enhances speed of the system by 74.1% compared to the conven-tional Wallace Tree multiplier, while 24.1 % reduction was achieved in the delay of the system relative to Wallace tree multiplier with 16-bit adder with one of the 8-2 adder compressors.Â Â